Comportamento estrutural de pilares mistos tubulares circulares submetidos à flexo-compressão - Santini, Ândrey Teston (2021)
Steel-concrete composite columns have many advantages over steel columns and reinforced concrete columns due to their high compressive strength, because the occurrence of local buckling in the steel tube is reduced due to the restriction caused by the concrete to the steel tube, and likewise, due to the ductility of the concrete caused by the confinement effect caused by the steel tube. Steel-concrete composite columns that use tubular sections are advantageous because their aesthetic appearance and advanced mechanical performance. When tubular section is circular, there is a gain in the confinement effect when compared to other sections. Several studies investigated the behavior of concrete filled steel tube (CFST), submitted to concentric force. However, when a column is subjected to an eccentric force, it has been noticed a loss in the confinement effect, caused by the increase of the curvature in the length of the cross-sectional session. In this case, the structural design is affected by the interaction between axial forces and bending moments. This study presents an analysis of 557 circular CFST submitted to concentric axial load and 274 circular CFST submitted to eccentric axial load, experimentally tested, obtained through bibliography. The influence of parameters: global slenderness index, local slenderness index, steel yield strength, concrete compressive strength and eccentricity index; was investigated under the structural behavior of circular tubular composite columns. The results were evaluated using performance indices: strength index, confinement factor and concrete contribution index. A numerical analysis was developed using the Finite Element (FE) method and Ansys Mechanical APDL Software, including composite columns with high strength steel and ultra high strength concrete, with satisfactory results. A statistical approach was carried out evaluating the parameters that exert the major influence on a wide range of composite columns, indicating that eccentricity is the most significant factor on the performance of circular CFST. A statistical approach was carried out to evaluate the parameters that have a major influence on the behavior of composite columns, indicating that eccentricity is the most significant factor affecting the performance of circular CFST.